ANALISIS PENGARUH IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. TANJUNG RHU PLANTATION AND PRODUCTS - B11212054, SUPARDI (Universitas Tanjungpura, 2014)
This study was conducted to determine whether the organizational climate which consists of structure, standards, responsibility, recognition, support, and commitment affect the employee job satisfaction either partially or simultaneously at PT. Tanjung Rhu Plantation and Producs. The population in this study were all employees of PT. Tanjung Rhu Plantation and Products, amounting to 295 people. The method used is the method of associative - causal with a total sample of 75 people. Analytical tool in this study is multiple linear regression. Based on the partial test (t test) result that the Standard (X2), Commitment (X6) and structure (X1) significantly influence employee job satisfaction and a more dominant variable effect on job satisfaction of employees at PT. Tanjung Rhu Plantation and Products is variable (X2) Standards. Partially Responsibility (X3), Recognition (X4), Support (X5) had no significant effect on job satisfaction of employees in PT. Tanjung Rhu Plantation and Products . The results of hypothesis testing using simultaneous test analysis (F test) obtained the result that the structure (X1), Standard (X2), Responsibility (X3), Recognition (X4), Support (X5), and Commitment (X6) together significant effect on job satisfaction of employees at PT. Tanjung Rhu Plantation and Products. Keywords : Organizational Climate, Job Satisfaction